Odpowiedzi

Najlepsza Odpowiedź!
2010-04-13T15:03:34+02:00
1) 3x+5 = 2x
3x - 2x = -5
x = -5
spr. 3*(-5) + 5 = 2*(-5)
-15 + 5 = -10
-10 = -10
2) 1/2 - x = -1/2x
-x + ½x = -½
-½x = -½ /*(-2)
x = 1
spr. ½ - 1 = -½*1
-½ = -½
3) 4 - x = 1,3
-x = 1,3 - 4
-x = -2,7 /:(-1)
x = 2,7
spr. 4 - 2,7 = 1,3
1,3 = 1,3
4) -(x-1) = 2
-x +1 = 2
-x = 1 /:(-1)
x = -1
spr. -(-1 - 1) = 2
-(-2) = 2
2 = 2
5) 3(x - 2) = x
3x - 6 = x
3x - x = 6
2x = 6 /:2
x = 3
spr. 3(3-2) = 3
3*1 = 3
3 = 3
2010-04-13T15:14:54+02:00
1) 3x+5 = 2x
3x-2x=-5
x=-5
spr. P=3*(-5)+5=-10
L=2*(-5)=-10
L=P
2) 1/2 - x = -1/2x
-x+1/2x=1/2 /*2
-2x+1x=1
-x=1 /:(-1)
x=-1
spr. P=1/2-(-1)=1/2+1=1i 1/2
L=-1/2*(-1)= 1i 1/2
L=P
3) 4 - x = 1,3
-x=1,3-4
-x=-2,7/:(-1)
x=2,7
spr. P=4-2,7= 1,3
L=1,3
L=P
4) -(x-1) = 2
-x+1=2
-x=2-1
-x=1/:(-1)
x=-1
spr. P=-(-1-1)=1+1=2
L=2
L=P
5) 3(x - 2) = x
3x-2=x
3x-x=2
2x=2/:2
x=1
spr. P=3(1-2)=3-2=1
L=1
L=P